Epitope Mapping and Fine Specificity of Human T and B Cell Responses for Novel Candidate Blood-Stage Malaria Vaccine P27A - Geiger, Kristina M.; Guignard, Daniel; Yang, Che; Bikorimana, Jean-Pierre; Correia, Bruno E.; Houard, Sophie; Mkindi, Catherine; Daubenberger, Claudia A.; Spertini, François; Corradin, Giampietro; Audran, Régine (Frontiers in Immunology, 2020)
P27A is a novel synthetic malaria vaccine candidate derived from the blood stage Plasmodium falciparum protein Trophozoite Exported Protein 1 (TEX1/PFF0165c). In phase 1a/1b clinical trials in unexposed adults in Switzerland and in pre-exposed adults in Tanzania, P27A formulated with Alhydrogel and GLA-SE adjuvants induced antigen-specific antibodies and T-cell activity, GLA-SE inducing significantly stronger humoral response than Alhydrogel. Here, we took the advantage of having groups of pre-exposed and unexposed subjects that received identical vaccine formulations to address comparisons between populations and adjuvants in the cellular and humoral response to P27A in term of fine specificity and affinity. Globally, fine specificity of the T and B cell responses shows preferred recognized sequences and did not highlight major differences between adjuvants or populations. Affinity of anti-P27A antibodies was around 10-8 M in all groups. Pre-exposed volunteers presented anti-P27A with higher affinity than unexposed. Increasing the dose of GLA-SE from 2.5 to 5 mcg in pre-exposed volunteers improved anti-P27A affinity and decreased the number of recognized epitopes. These results revealed signs of higher maturation of the humoral response in pre-exposed volunteers, particularly when immunized with P27A formulated with 5 mcg GLA-SE.